Synergistic interaction of Deltex and Hrp48 leads to JNK activation. (28th January 2019) - Dutta, Debdeep; Mutsuddi, Mousumi; Mukherjee, Ashim
Abstract: The communication among the cells plays a seminal role in metazoan development by coordinating multiple cellular processes that, in turn, helps in the maintenance of biological homeostasis. Our previous study demonstrated that Dx and Hrp48 together downregulate Notch signaling and induce cell death in Drosophila . To understand the signaling events behind the Dx and Hrp48‐induced cell death in a greater detail, we performed a set of genetic experiments followed by immunocytochemical analyses. Our data revealed that Dx along with Hrp48 induced JNK activation and consequently cell death in the eye tissue. Additionally, using genetic and molecular approaches, we identified the domain of Dx protein responsible for its synergistic activity with Hrp48. Altogether, our analyses suggest that coexpression of Dx and Hrp48 activates JNK pathway to induce cell death in eye disc of Drosophila melanogaster .